Poor nutritional status correlates with mortality and worse postoperative outcomes in patients with femoral neck fractures: an observational study in a large UK teaching hospital. (1st January 2021) - O'Leary, Lawrence; Jayatilaka, Lara; Leader, Ross; Fountain, James
Abstract : Aims: Patients who sustain neck of femur fractures are at high risk of malnutrition. Our intention was to assess to what extent malnutrition was associated with worse patient outcomes. Methods: A total of 1, 199 patients with femoral neck fractures presented to a large UK teaching hospital over a three-year period. All patients had nutritional assessments performed using the Malnutrition Universal Screening Tool (MUST). Malnutrition risk was compared to mortality, length of hospital stay, and discharge destination using logistic regression. Adjustments were made for covariates to identify whether malnutrition risk independently affected these outcomes. Results: Inpatient mortality was 5.2% (35/678) in the group at low risk of malnutrition, 11.3% (46/408) in the medium-risk group, and 17.7% (20/113) in the high-risk group. Multivariate analysis showed each categorical increase in malnutrition risk independently predicted inpatient mortality with an odds ratio (OR) of 1.59 (95% confidence interval (CI) 1.14 to 2.21; p = 0.006). An increased mortality rate persisted at 120 days post-injury (OR 1.64, 95% CI 1.20 to 2.22; p = 0.002). There was a stepwise increase in the proportion of patients discharged to a residence offering a greater level of supported living. Multivariate analysis produced an OR of 1.34 (95% CI 1.03 to 1.75; p = 0.030) for each category of MUST score. Median length of hospital stay increased with a worse MUST score: 13.9 days (interquartile range (IQR) 8.2 to 23.8) in the low-risk group; 16.6 days (IQR 9.0 to 31.5) in the medium-risk group; and 22.8 days (IQR 10.1 to 41.1) in the high-risk group. Adjustment for covariates revealed a partial correlation coefficient of 0.072 (p = 0.008). Conclusion: A higher risk of malnutrition independently predicted increased mortality, length of hospital stay, and discharge to a residence offering greater supported living after femoral neck fracture. Cite this article: Bone Joint J 2021;103-B(1):164–169.